EFEKTIVITAS PUPUK DAN BARIS TANAM PADA VERTIKULTUR TERHADAP TANAMAN PAKCOY DI LAHAN KERING: EFEKTIVITAS PUPUK DAN BARIS TANAM PADA VERTIKULTUR TERHADAP TANAMAN PAKCOY DI LAHAN KERING - Joachim Anasto Seran; Syprianus Ceunfin; Wilda Lumban Tobing; Azor Yulianus Tefa; Deseriana Bria (Cemara Education and Science, 2025)
This study aims to determine the effectiveness of fertilizer and planting rows in vertical culture on the growth and yield of pak choi plants in vertical cultivation of fertigation systems in dry land. This study used a 2-factor Split Plot Design. Fertilizer concentration as the main plot consisting of: urea 1 g/L + POC 40 mL/L + BPN 10 mL/L; urea 0.75 g/L + POC 30 mL/L + BPN 7.5 mL/L; urea 0.5 g/L + POC 20 mL/L + BPN 5 mL/L; and urea 0.25 g/L + POC 10 mL/L + BPN 2.5 mL/L planting row intervals as sub-plots consisting of: first planting row, second planting row, and third planting row. There were 12 treatment combinations that were repeated 3 times, so that 36 total treatments were obtained. This study has shown that the treatment of urea fertilizer 0.75 g/L + POC 30 mL/L + BPN 7.5 mL/L in the second planting row is able to increase the growth and yield of pak choi plants in dry land through the application of vertical cultivation system with fertigation.